K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Bài 1: 

\(=\dfrac{-3-39}{42}+\dfrac{-6-11}{17}-\dfrac{1}{6}=-\dfrac{119}{48}\)

Bài 2: 

=>x:5=-13/20

hay x=-65/20=-13/4

30 tháng 10 2021

\(17\times17+17\times44+39\times17=17\left(17+44+39\right)\)

\(=17\times100=1700\)

30 tháng 10 2021

17x17+17x44+39x17

= 17x(17+44+39)

= 17x(100)

=1700

Ta có: \(\dfrac{-1}{3}\cdot\dfrac{141}{17}-\dfrac{39}{3}\cdot\dfrac{-1}{17}\)

\(=\dfrac{-1}{3}\cdot\dfrac{141}{17}-\dfrac{-1}{3}\cdot\dfrac{39}{17}\)

\(=\dfrac{-1}{3}\cdot\left(\dfrac{141}{17}-\dfrac{39}{17}\right)\)

\(=\dfrac{-1}{3}\cdot6=-2\)

29 tháng 3 2017

a) 500                  

b) 2303                

c) 537 

d) 35000

Bài 1: 

\(=\dfrac{-3-39}{32}+\dfrac{-6-11}{17}+\dfrac{-1}{6}=-\dfrac{21}{16}+\dfrac{-1}{6}-1=-\dfrac{119}{48}\)

Bài 2: 

\(\Leftrightarrow x:5=-\dfrac{13}{20}\)

hay x=-13/4

28 tháng 3 2019

\(M=\frac{17}{5}\cdot\frac{1}{2}\cdot\frac{10}{17}\cdot\frac{-1}{2^3}\)

\(=\frac{17}{5}\cdot\frac{10}{17}\cdot\frac{1}{2}\cdot\frac{-1}{8}\)

\(=\frac{17\cdot10}{5\cdot17}\cdot\frac{1\cdot(-1)}{2\cdot8}\)

\(=\frac{1\cdot2}{1\cdot1}\cdot\frac{1\cdot(-1)}{2\cdot8}\)

\(=2\cdot\frac{-1}{16}=\frac{2\cdot(-1)}{16}=\frac{1\cdot(-1)}{8}=\frac{-1}{8}\)

28 tháng 3 2019

\(M=\frac{17}{5}.\frac{1}{2}.\frac{10}{17}.\frac{-1}{2^3}\)

\(\Leftrightarrow M=\frac{17}{5}.\frac{1}{2}.\frac{10}{17}.\frac{-1}{8}\)

\(\Leftrightarrow M=\left(\frac{17}{5}.\frac{10}{17}\right)\left(\frac{1}{2}-\frac{-1}{8}\right)\)

\(\Leftrightarrow M=2.\frac{-1}{16}\)

\(\Leftrightarrow M=\frac{-2}{16}=\frac{-1}{8}\)

23 tháng 2 2022

\(\dfrac{17}{5}.\dfrac{-31}{125}.\dfrac{1}{2}.\dfrac{10}{17}.\dfrac{-1}{2^3}\\= \left(\dfrac{17}{5}.\dfrac{10}{17}\right)\left(\dfrac{-31}{125}.\dfrac{-1}{8}\right).\dfrac{1}{2}\\ =2.\dfrac{31}{1000}.\dfrac{1}{2}\\ =\left(2.\dfrac{1}{2}\right).\dfrac{31}{1000}\\ =1.\dfrac{31}{1000}\\ =\dfrac{31}{1000}\)

15 tháng 8 2019

\(A=\frac{2}{7}+\frac{-3}{8}+\frac{11}{7}+\frac{1}{3}+\frac{1}{7}+\frac{5}{-8}\)

\(A=\left(\frac{2}{7}+\frac{11}{7}+\frac{1}{7}\right)+\left(\frac{-3}{8}+\frac{5}{-8}\right)+\frac{1}{3}\)

\(A=2-1+\frac{1}{3}\)

\(A=\frac{4}{3}\)

\(B=\frac{3}{17}+\frac{-5}{13}+\frac{-18}{35}+\frac{14}{17}+17\)

\(B=\left(\frac{3}{17}+\frac{14}{17}\right)+\frac{-5}{13}+\frac{-18}{35}+17\)

\(B=1+\frac{-5}{13}+\frac{-18}{35}+17\)

\(B=18+\frac{-5}{13}+\frac{-18}{35}\)

\(B=\frac{7781}{455}\)